Penyisihan Cod Pada Limbah Cair Sawit Menggunakan Chlorella Sp. Yang Diimmobilisasi Dalam Flat-Fotobioreaktor Dengan Sistem Semikontinu - Denada Curie; Shinta Elystia; Said Zul Amraini (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Palm oil mill effluent is one of the by-products of palm oil producing which contains high organic matter, so it needs a treatment before discarded into the water. One of the treatment method that can be done is by utilizing the organic matter into a source of nutrition for the growth of microalgae Chlorella sp. This study is conducted to determine the ability of microalgae Chlorella sp. in removing COD of palm mill effluent and knowing the specific growth rate of cells Chlorella sp. during the allowance process. Chlorella sp. has a small size, smooth, low density and easily carried by the flow of wastewater, so the cells Chlorella sp. immobilized with calcium alginate to make the cells are more stable and protected from the pressure of wastewater. In this study, the continuous system is carried out by replacing wastewater with fresh wastewater at variations of the wastewater volume replacments 0, 25, 50, 75 (% v/v) at 24 hours contact time. The removing process is carried out for 7 days with irradiation on the light intensity 5000 ± 300 lux and the lighting period (L:D) 12:12. The stirring process uses an aerator with 3 L/minute aeration discharge. The results showed that the 25% wastewater volume replacement was able to put aside the best COD with removal efficiency 85.71% at the best removing process detention time 7 days. Keywords: Chlorella sp., Semicontinuous systems, Palm Oil Mill Effluent, COD, Contact Time.